Analyzing e-fulfillment - Cheah, Yvonne Pek Lee. (2008)
In this thesis, logistics concepts have been defined and the recent trends in logistics have been explored. The importance of E-fulfillment in the growth of E-business has been discussed. By finding out the complete process of fulfillment and opportunity to integrate this process with an integrated electronic system, an E-fulfillment model is proposed.